Manhaj Fiqih Mua'malah National Sharia Board-Indonesian Council of Ulama - Irham Khalid; Andri Soemitra (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Along with the development of the Islamic economy in today's society, the legal questions that arise regarding the sharia economy continue to grow along with the development of the Islamic banking and finance industry lately. fiqh Mu'amalah. Then MUI as an institution that has the authority to issue fatwas is very interesting to study. The fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI) has become an inseparable part of the development of the Islamic finance industry in Indonesia. Many of the DSN-MUI Manhaj Fatwas use Islamic legal solutions as their basis. This research uses qualitative research and divides it into 2 themes of discussion, namely 1. The DSN-MUI Manhaj Fatwa method, 2. The role, significance and position of the DSN-MUI fatwa.